2002
DOI: 10.1038/sj.mp.4000958
|View full text |Cite
|
Sign up to set email alerts
|

Segmental linkage disequilibrium within the dopamine transporter gene

Abstract: The dopamine transporter gene (DAT) has been implicated in a variety of disorders, including bipolar disorder, attention-deficit hyperactivity disorder, cocaine-induced paranoia, Tourette's syndrome, and Parkinson's disease. As no clear functional polymorphism has been identified to date, studies rely on linkage disequilibrium (LD) to assess the possible genetic contribution of DAT to the various disorders. A better understanding of the complex structure of LD across the gene is thus critical for an accurate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 27 publications
1
44
1
1
Order By: Relevance
“…There may be other functional polymorphisms in the SERT gene involved in AN that are not in linkage disequilibrium with 5-HTTLPR. A lack of linkage disequilibrium between the ends of a gene is demonstrated in the dopamine transporter gene (Greenwood et al, 2002) and dopamine 2 receptor (DRD2) gene (Gelernter et al, 1998). Recently, Kim et al (2002) also reported that autistic disorder may have stronger association at locations other than at 5-HTTLPR.…”
Section: Discussionmentioning
confidence: 98%
“…There may be other functional polymorphisms in the SERT gene involved in AN that are not in linkage disequilibrium with 5-HTTLPR. A lack of linkage disequilibrium between the ends of a gene is demonstrated in the dopamine transporter gene (Greenwood et al, 2002) and dopamine 2 receptor (DRD2) gene (Gelernter et al, 1998). Recently, Kim et al (2002) also reported that autistic disorder may have stronger association at locations other than at 5-HTTLPR.…”
Section: Discussionmentioning
confidence: 98%
“…An alternative explanation, is that the 10-repeat allele is not the causative allele itself, but rather 'tags' a nearby functional variant that is only partially correlated with the 10-repeat allele. Evidence for this comes from the observation in several studies that specific DAT1 haplotypes containing the 10-repeat allele confer risk for ADHD [3,4,6,13,16,17]. A c c e p t e d M a n u s c r i p t signal fell into two distinct groups of markers at the 3'and 5' ends of the gene.…”
Section: Introductionmentioning
confidence: 99%
“…', which differ by the first 6 SNPs, and 12 rare haplotypes define the haplotype structure of block 1, as we have previously suggested (data not presented; see Figure 2b for haplotypes). 11,19 The haplotypes of block 2 belong to two ancestral groups, 'CCC' and 'GG? ', which are differentiated by the first two SNPs and encompass the majority of haplotypes (data not presented; see Figure 2b for haplotypes).…”
Section: Ld and Cladistic Analysesmentioning
confidence: 99%
“…6,11 An additional eight SNPs of those newly identified were chosen for genotyping based on location and genotyping feasibility. Genotyping of these SNPs in the combined sample of 120 trios was performed by Qiagen Genomics with the Masscode System, which uses cleavable mass spectrometry tags in multiplex reactions.…”
Section: Snp Genotyping and Haplotype Constructionmentioning
confidence: 99%
See 1 more Smart Citation